The Measurement of Internet Availability and Quality in the Context of the Discussion on Digital Divide - Lüdering, Jochen; Justus Liebig University Giessen (My University, 2014)
This paper discusses measures of Internet quality and availability used and usable in the analysis of the so called digital divide. The usage of the share of Internet users in the population - widely used in economic analysis - can easily be misleading in this debate. Based on this measure one might get the idea that the digital divide is narrowing, as some industrialized countries are already close to a share of 100 % Internet users in the population, while the ratio of Internet users to total populations is still growing for developing countries. I argue that one should focus more on the study of Internet quality and quantity provided in a demand and supply model of infrastructure. To this end, I introduce a new latency-based measure to judge the quality of Internet, based on a novel data set, and compare it to related measures. The results indicate that it may indeed be useful to measure Internet quality across countries. The possibility to examine the effects of different determinants on individual quantiles is particularly interesting. ICT investment appear to be stronger correlated with lower latency in the upper part of the distribution, while the effect on the lower part is less pronounced. In addition we find that population density is an important determinant of latency - an argument which is brought up in the theoretical discussion on ICT investment but - to my knowledge - not found empirically to date.
Keywords: digital divide; internet; telecommunication infrastructure; measurement; bandwidth; ddc:300